2021
DOI: 10.48550/arxiv.2103.12770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distributed Visual-Inertial Cooperative Localization

Abstract: In this paper we present a consistent and distributed state estimator for multi-robot cooperative localization (CL) which efficiently fuses environmental features and loopclosure constraints across time and robots. In particular, we leverage covariance intersection (CI) to allow each robot to only track its own state and autocovariance and compensate for the unknown correlations between robots. Two novel different methods for utilizing common environmental temporal SLAM features are introduced and evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…We observe that more exciting new directions are still being discovered, considering that recent approaches such as (Tian et al, 2021b) have been shown to outperform, both in accuracy and convergence rate, the well established Distributed Gauss-Seidel pose graph optimization method (Choudhary et al, 2017a) reused in many state-of-the-art C-SLAM systems such as (Cieslewski et al, 2018;Lajoie et al, 2020;Wang et al, 2019). Those promising approaches also include the majorization-minimization technique from (Fan and Murphey, 2020), the consensus-based 3D pose estimation technique inspired by distributed formation control from (Cristofalo et al, 2019;Cristofalo et al, 2020), and (Zhu et al, 2021) distributed estimator based on covariance intersection.…”
Section: Other Estimation Techniquesmentioning
confidence: 99%
“…We observe that more exciting new directions are still being discovered, considering that recent approaches such as (Tian et al, 2021b) have been shown to outperform, both in accuracy and convergence rate, the well established Distributed Gauss-Seidel pose graph optimization method (Choudhary et al, 2017a) reused in many state-of-the-art C-SLAM systems such as (Cieslewski et al, 2018;Lajoie et al, 2020;Wang et al, 2019). Those promising approaches also include the majorization-minimization technique from (Fan and Murphey, 2020), the consensus-based 3D pose estimation technique inspired by distributed formation control from (Cristofalo et al, 2019;Cristofalo et al, 2020), and (Zhu et al, 2021) distributed estimator based on covariance intersection.…”
Section: Other Estimation Techniquesmentioning
confidence: 99%